Induction Mapping of the 3D-Modulated Spin Texture of Skyrmions in Thin Helimagnets - Schneider, S.; Wolf, Daniel; Stolt, M. J.; Jin, Song; Pohl, D.; Rellinghaus, Bernd; Schmidt, M.; Buechner, B.; Goennenwein, S. T. B.; Nielsch, Kornelius; Lubk, A. (Physical Review Letters, 2018)
Envisaged applications of Skyrmions in magnetic memory and logic devices crucially depend on the stability and mobility of these topologically nontrivial magnetic textures in thin films. We present for the first time quantitative maps of the magnetic induction that provide evidence for a 3D modulation of the Skyrmionic spin texture. The projected in-plane magnetic induction maps as determined from in-line and off-axis electron holography carry the clear signature of Bloch Skyrmions. However, the magnitude of this induction is much smaller than the values expected for homogeneous Bloch Skyrmions that extend throughout the thickness of the film. This finding can only be understood if the underlying spin textures are modulated along the out-of-plane z direction. The projection of (the in-plane magnetic induction of) helices is further found to exhibit thickness-dependent lateral shifts, which show that this z modulation is accompanied by an (in-plane) modulation along the x and y directions.
CRIS-Team Scopus Importer:2022-04-14